(untitled) (Cardiovascular Journal, 2014)
Background: Aim of the study was to evaluate the primary procedural success of percutaneous coronary intervention (PCI) of de-novo coronary artery lesion by using Bioabsorbable Vascular Scaffold (BVS) ABSORB stents eluting Everolimus. Methods: Total 16 patients were enrolled in this very preliminary study of BVS absorb. Among them, Male: 11 and Female: 5. Total 20 stents were deployed. Mean age were for Male: 56 yrs, for Female: 60 yrs. Associated coronary artery disease (CAD) risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive family history (FH) for CAD and Smoking. Patients were followed up clinically. Results: Among the study group; 13 (81%) were Dyslipidemic, 10(62.5%) were hypertensive; 6 (37.5%) patients were Diabetic, FH 3(18.75%), and 2(18%) were all male smoker. Female patients were more obese [Body Mass Index (BMI) M 25: F 27] and developed CAD in advance age. A common stented territory was for left anterior descending artery (LAD): 6 (37.5%), left circumflex artery (LCX) 5 (25%), right coronary artery (RCA) 6(37.5%). One patient had both LCX and LAD stenting. Total 3 patients had double/overlapping stent in RCA lesion. Territory wise distributions of BVS ABSORB stent were for LAD 6(30%), RCA 9 (45%), and LCX 5 (25%). There was no periprocedural or postprocedural complication. Conclusion: BVS ABSORB Everolimus eluting vascular scaffold showed favorable clinical outcome without any major cardiac events (acute or late stent thrombosis, MI or death) over a period of 9 month. Thus, BVS ABSORB would be favorable alternative to other available drug eluting metallic stents. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18352 Cardiovasc. j. 2014; 6(2): 122-126